ADOPTION OF AUGMENTED REALITY TECHNOLOGY IN LEARNING PLATFORM CASE STUDY: KOOKA - Fikri Ganjar, Ibnu
Augmented reality (AR) is the integration between digital world with the user’s environment that allowing real-world to seamlessly interact with digital components. In the meantime, the development of augmented reality in Indonesia doesn’t massive as another country in Southeast Asia. Augmented reality has become a modern technology that show the existence, especially in Indonesia. Despite the commercialization of augmented reality technology can be measured as excessive in community. Yet, the community are does not realize about augmented reality technology existence. Nowadays, the application of Augmented Reality (AR) already leveraged into education industry, many learning platforms start to use AR to enhance the learning experience and engagement and Kooka company is one of company that provide learning platform by using Augmented Reality (AR) technology. Since, this Augmented Reality (AR) still new to be applied in learning platform, this research will assess the adoption of augmented reality learning platform. To analyze what are the factors that influence the adoption of augmented reality in learning platform, this research use modified Technology Acceptance Mode (TAM) which consists of two dimension. The first dimension which is Augmented Reality (interactive and informative technology and augmented reality as playfulness technology) and Individual Differences dimension which are (personal innovative and consumer knowledge). The data was collected using survey method towards 216 samples and analyzed by using SEM-PLS. The result shows that both of dimension has a significant affect towards perceive usefulness. The users did not concern that their innovative capabilities affect the ease of use towards using augmented reality. But it has a significant impact towards attitude that accompanied to intention to use of this learning platform. Hopefully, the augmented reality technology has a significant effect on increase the willingness of student in learning through implemented augmented reality technology on they learning as interesting tools.